The Communication Strategies Used in English Classroom Presentation by the English Education Students of UNIMUDA Sorong - Nurteteng Nurteteng (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2018)
The study attempts to analyze the types of communication strategies used in English classroom presentation by the English education students of UNIMUDA Sorong and the reasons why they used the strategy. The study took place at UNIMUDA Sorong in TEFL class where 30 students were participated and observed during their presentation activity in this subject. The study employed descriptive method, where the data obtained through open interviewed and video recording. The result showed that from twelve features of communication strategies, there are six of them that the students used during presentation. They are appoximation, circumlocation, examplification, word coinages, code switching and use fo fillers. Circumlocation was used because the students wanted to make direct contact to the students in order to make the successful teaching and learning process. Examplification was used because it can reflect the meaning of the concept. Word coinages was used because they might forget the appropriate words/term. Code switching was used because they felt more comfortable in case she combined between Bahasa Indonesia and the English language. Use of fillers was used because the strategy was very significant particularly second or foreign language speaker. The most frequently communication strategy that the students used is use of fillers.